Sustainable Tourism Development Guidelines for the Sairee Community Muang District, Chumphon Province - Klaiudom, Pongchan (International Journal of Engineering and Technology, 2019)
This research aims to: 1) study behavior of tourists visiting the Sairee Beach, Muang District, Chumphon Province; 2) evaluate the potential of tourism in the Sairee Beach and; 3) develop sustainable tourism development guidelines for the Sairee community. Quantitative and qualitative research methods were applied for the study. In addition, the research sample, 400 Thai tourists in the Sairee community, were randomly selected. Questionnaires, a semi-structured interview, and a focus group of various stakeholders were employed to collect data.The results showed that behaviors of tourists visiting the Sairee community were as follows: most of them had been there 2-3 times mostly in January-March, traveling with friends and using private car, and spending a day there; and most of the expenses were for transportation. The reason for visiting was the reputation of the place (51.8 %) and they expected to come back in the future (66%). Furthermore, average level of tourism potential in the Sairee Beach for 8 aspects namely; attractiveness, accessibility, activities, accommodation, environment, management, facilities and value from tourism was at moderate level (Â = 3.23 S.D. = 0.53). When considering each aspect, it was found that the attractiveness was at a high level (Â = 3.61 S.D. = 0.63) followed by activities (Â = 3.38 S.D. = 0.69), environment (Â = 3.27 S.D. = 0.68), accommodation (Â = 3.23 S.D. = 0.62), value for tourism (Â = 3.16 S.D. = 0.74), accessibility (Â = 3.11 S.D. = 0.87), management (Â = 3.08 S.D. = 0.68) and facilities (Â Â = 3.01 S.D. = 0.65), respectively. In Addition, the guidelines for sustainable tourism development in the Sairee Beach consists of 5 issues. Firstly, tourism resource of the community should be developed, maintained, and improved, sufficiently. Tourism professionalsâ€™ quality should be concerned to enhance service quality. Furthermore, tourism environment and natural resources in the community should be effectively managed, while, facilities and infrastructureâ€™s quality should be improved and expanded for tourism. Finally, increasing the participation of various stakeholders in tourism management, promoting tourism activities and developing souvenir and tourist shops should be addressed in tourism planning of the Sairee community.Â Â Â Â